Comprehensive Pan-Cancer Analysis of TRPM8 in Tumor Metabolism and Immune Escape - Zhang, Wei; Qiao, Xin-yu; Li, Qian; Cui, Chun; Qiao, Chen-meng; Shen, Yan-qin; Zhao, Wei-jiang (Frontiers in Oncology, 2022)
Background: Transient receptor potential melastatin 8 (TRPM8) modulates tumor biology and sensitivity to treatment. The present study aimed to determine the part it plays in tumor immunity and physiology using pan-cancer analysis. Method: Data from the GTEx, CCLE, TISIDB, GSCA, cBioportal, and TCGA databases were collected using Estimate, Scanneo, and GSEA and the associations between TRPM8 and prognosis, molecular subtypes, mutational burden, microsatellite instability, immune gene functions, and drug sensitivity were analyzed in 33 tumor types. Result: TRPM8 levels were found to be elevated in most tumors, particularly in solid tumors, with variations according to clinical stage. Mutation frequency was greatest in endometrial carcinoma. High levels of TRPM8 were linked to unfavorable prognosis, immune cell infiltration, and the tumor microenvironment, as well as correlating with abnormalities in the transcription and levels of genes associated with immunity and DNA repair. TRPM8 was also linked to unfavorable patient outcomes and cancer-associated signaling. Conclusions: TRPM8 is strongly associated with tumor physiology and immunity. The Pan-Cancer analysis suggests the potential of TRPM8 as a treatment target or biomarker for determining the prognosis of a specific type of cancer.